Analisis Problematika Proses Pembelajaran IPA di Sekolah Dasar - I Made Ari Winangun (Edukasi: Jurnal Pendidikan Dasar, 2022)
Science learning in elementary school experiences various basic problems. Based on the exploration results, it was found that: (i) the problems of implementing the learning model experienced were the teacher's mind set and comfort zone in teaching; (ii) the problem with using learning media is the teacher's ability to observe the characteristics of students; (iii) the problem of science laboratory learning design in elementary schools is optimizing the existence of laboratory facilities and/or infrastructure to improve the quality of learning; and (iv) the problems of facilities in science learning are the availability of learning resources, flexibility and accessibility of learning resources, and the existence of science practicum facilities and/or infrastructure in elementary schools.